Domestic violence legislation: Awareness and support in Latvia, Russia and Ukraine - Maria Perrotta Berlin; Pamela Campa; Marija Krumina; Elena Paltseva; Anna Pluta; Solomiya Shpak (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2022)
A large literature, that received further momentum during the Covid-19 pandemic, evaluates legislative initiatives to combat domestic violence. For legislation to induce a reduction in crime, information and awareness among the population are in many cases necessary. This study investigates the factors that correlate with awareness and support for domestic violence legislation in three countries that introduced recent reforms. We find that men, younger cohorts, married and less educated people are less well-informed, as well as minority language speakers. Studies of legislation awareness are important to motivate and target information campaigns.
Keywords: 330; Domestic violence; legislation awareness; reforms; norms